481. Risk Factors and Clinical Outcomes of Candidemia Associated with Severe Coronavirus Disease 2019 (COVID-19). (15th December 2022) - Bhowmick, Tanaya; Jagpal, Sugeet; Varughese, Tilly; Patel, Purvi; Jen, Polly; Maxwell, Tyler; Tatem, Luis; (Claudia) Choi, Seohyun; Walker, Amanda; Eidensohn, Yehuda; Smoke, Steven; McCracken, James A; et al.
Abstract: Background: COVID-19 can cause serious illness requiring multimodal treatment of the viral infection and its associated complications, including the potential for secondary infections. Studies have suggested an increased risk of fungal infections, including candidemia following severe COVID-19 though understanding of risk factors and clinical outcomes remains unclear. Methods: A multi-center, case-control study of patients with severe COVID-19 was conducted to evaluate risk factors and clinical outcomes in patients who developed candidemia between August 2020 to August 2021. Risk factors associated with candidemia and mortality were characterized using multivariate analyses. Results: A total of 275 patients were enrolled in the study, including 91 patients with severe COVID-19 and subsequent candidemia and 184 patients with severe COVID-19 without candidemia. Most patients received antibiotics prior to candidemia episode (93%), while approximately one-quarter of all patients received biologic for COVID-19. In-hospital mortality was significantly higher in the case group compared to the control group (68% vs 40%, P < 0.01). Multivariable logistic regression revealed that the use of central lines, biologic and paralytic therapy were independent risk factors for candidemia. The presence of candidemia, older age, central line use, and intensive care unit admission were significantly associated with mortality. Demographics and Baseline Characteristics of Study Patients with SARS-CoV-2 Positive With or Without Candidemia Hospitalization Details and Outcomes Conclusion: Clinicians should be aware of the possibility of development of candidemia in hospitalized older patients with severe COVID-19 and should closely monitor those patients at risk. Risk factors for developing candidemia in the setting of COVID-19 are largely consistent with classic risk factors previously identified. Disclosures: Tanaya Bhowmick, MD, Gilead: Grant/Research Support|Shinogi: Advisor/Consultant Steven Smoke, PharmD, BCPS, BCIDP, Karius: Advisor/Consultant|Shionogi: Advisor/Consultant.